PHENOMENOLOGICAL STUDY: THE INTEGRATION OF TECHNOLOGY AS MEDIA IN TEACHING AND LEARNING PROCESS BASED ON STUDENTS’ PERCEPTION - Irma Manda Negara (Jurnal Ilmiah Spectral, 2019)
This research is a phenomenological study that identifying based on students’ perception and experiences about technology integration as media in the teaching-learning process. This research used descriptive qualitative, by conducting open interviews for students in teaching expertise at STBA Pontianak. Based on the results of the interview, students argued that by using learning media, learning activities become more effective and efficient and also can increase student involvement and motivation in learning. Learning media also can stimulate students' attention and thinking ability, thus helping students understand the material delivered by the teacher. There are several types of technology-based learning media that can be used in learning, including computer equipment, internet, YouTube, website, email, etc. With the use of technology as a learning media, the learning process becomes more effective and efficient and can improve the quality of learning. The utilization of technology as learning media makes it easy for teachers and students to explore learning material according to what they need. Therefore, the application should be supported with adequate facilities and tailored to the needs of students. In the selection of technology as media must be adjusted to the material to be delivered. Then choosing technology from the media needed an educator must study the theory and information that have been developed. By using technology-integrated media, it is hoped that in the class situations are not boring so learning can achieve goals and students easily understand learning material